Assessment of information needs in public health in Germany: results of a nationwide survey. - A. Scheiber; R. Schneemann; R. Wischer (Information Research: An International Electronic Journal)
Since Public Health in Germany is a new multidisciplinary area, there is no well established informational infrastructure to offer researchers, as well as other experts, an overview of current research activities and recently published literature. Therefore, a preliminary study is assessing the informational needs in public health research and practice. A survey about the experience with online databases and demands for specific information resources was conducted in order to analyse the extent of problems experienced with information retrieval. The main conclusions of the survey findings are: (a) there is a serious demand for information filtering and information supply in Public Health in Germany, (b) some of the ‘’missed’’ databases do already exist, but are obviously not well known or accessible, thus indicating a need of promoting information resources and (c) although some of the respondents have had access to the Internet, only very few of them are using email or the world wide web to find and exchange information.